ALAM SEMULAJADI PADA FIGURA WANITA - Norhasmida, Binti Hasan (unimas, 2017)
In this research, the researcher will describe the nature. Next, explain more in depth about women and women's figures. Besides that, researchers will clarify about artists ceramic work related to women and have figures and referring artist Juliette Clovis reference. In addition, researchers using observation and experimentation to perfect Glaze applied to the ceramic work and previous studies referring to collect the data. At the end of the study, a ceramic work entitled "Natural In Women" will be presented to the audience.